Providing Clinical Experience for Preservice Chemistry Teachers Through a Homeschool Association Collaboration - Boesdorfer, Sarah (Innovations in Science Teacher Education, 2019)
The number of students homeschooled in the United States is steadily increasing, and parents of these students continue to look to community resources for their curriculum as they educate their children. As clinical experiences associated with two of their methods courses, preservice chemistry teachers teach a chemistry course twice a week to homeschooled students under the supervision of their methods instructor. The course is a collaboration between the Department of Chemistry and the local homeschool association (HSA), providing the homeschool students with high school chemistry instruction and experiences in the chemistry laboratory and providing preservice teachers with experiences teaching high school aged chemistry students. This article describes the design of this collaboration aligning it with the research literature of successful clinical experiences for the development of preservice teachers. In addition, initial evidence and feedback from teachers provides support for this collaboration as an effective alternative to traditional clinical experiences in typical high school settings for preservice science teachers. Challenges to carrying out this type of clinical experience are discussed along with tips for teacher educators looking for a different form of effective clinical experiences for their preservice teachers. While improvements continue to be made, the collaboration between the HSA and the methods courses has been successful for students, both homeschooled and preservice, and continues as a clinical experience at our university.